DISMINUCION DE DANLING BONDS SIN OXIDACION - Suárez Gómez, Alfonso; Departamento de Física, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
Measurement of electron paramagnetic resonance signal variation offour SiOx ' :fi1ms produced during the same evaporatiQn time and having different thickness was made. Although spin concentration· decay over time was lower in the Cr-Au-SiOx -A u capacitor (film Nº 2) 22.77% in eigth days as compared with the SiOx (film Nº l).Wich decaywas about 42% during the sametime, decrease _of spin concentration was observed as expected. This was not noticed in thefourth 8iOx-Au (film N2 4), wich fully covered witha gold layer, showed a substancial decrease of spin concentration 45.04% in the sametime. This suggests, for .the last film, that oxidation is not the cause of spin concentration decay, and enhances the theorythat the signal is dueto unpaired silicon electron wich acts as a Poole-Frenkel emision during d. c. conduction. The spin concentnttion was proportional to the film thickness.